THE SEMANTIC AND LINGUOCULTURAL ROLE OF LIVESTOCK LEXICON IN UZBEK AND ENGLISH - Mukhammadiyev Sukhrob Bakhtiyor ugli (Bright Mind Publishing, 2025)
This article investigates the livestock vocabulary of Uzbek and English from semantic and linguocultural perspectives. Drawing on semantic-field analysis and etymological reconstruction, it examines core terms for domesticated animals and their products, revealing divergent lexical strategies: a unified animal–product system in Uzbek versus a split terminology in English. Discourse analysis of proverbs, idioms, and ritual texts shows how these patterns mirror nomadic-pastoral and agrarian-industrial worldviews, respectively. Findings underscore the importance of livestock lexicon both as a repository of traditional knowledge and as a resource for ongoing linguistic creativity.
Keywords: Livestock lexicon; semantics; etymology; linguoculture; Uzbek; English.